2004
DOI: 10.1021/np049949f
|View full text |Cite
|
Sign up to set email alerts
|

Kulokekahilide-2, a Cytotoxic Depsipeptide from a Cephalaspidean Mollusk Philinopsis speciosa

Abstract: A cytotoxic depsipeptide, kulokekahilide-2 (1), was isolated from a cephalaspidean mollusk, Philinopsis speciosa. The structure elucidation of kulokekahilide-2 was carried out by spectroscopic analysis and chemical degradation. Kulokekahilide-2 showed potent cytotoxicity against several cell lines (P388, SK-OV-3, MDA-MB-435, and A-10 with IC50 values ranging from 4.2 to 59.1 nM) indicating cancer cell selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 34 publications
0
69
0
Order By: Relevance
“…These compounds belong to the mixed polyketide-polypeptide structural class, consisting of five amino acids (Ala, N Me-Phe, N Me-Gly, Ile, and N Me-Ala), one-hydroxy acid (2-hydroxy-isoleucic acid) and a unique extended polyketide moiety. The lagunamides are structurally related to the aurilide class of molecules, which include aurilides B ( 4 ) and C ( 5 ) and kulokekahilide-2 ( 6 ) (Chart 1) [13,14,15]. Aurilide ( 3 ), the first member of this class of molecules, was originally reported from the sea hare, Dolabella auricularia [16].…”
Section: Resultsmentioning
confidence: 99%
“…These compounds belong to the mixed polyketide-polypeptide structural class, consisting of five amino acids (Ala, N Me-Phe, N Me-Gly, Ile, and N Me-Ala), one-hydroxy acid (2-hydroxy-isoleucic acid) and a unique extended polyketide moiety. The lagunamides are structurally related to the aurilide class of molecules, which include aurilides B ( 4 ) and C ( 5 ) and kulokekahilide-2 ( 6 ) (Chart 1) [13,14,15]. Aurilide ( 3 ), the first member of this class of molecules, was originally reported from the sea hare, Dolabella auricularia [16].…”
Section: Resultsmentioning
confidence: 99%
“…Kulokekahilide-2 (82) (Fig. 9) is another potent auriliderelated compound initially isolated from the Hawaiian marine mollusk, Philinopsis speciosa (Nakao et al 2004). It is hypothesized that kulokekahilide-2 is biosynthesized by marine cyanobacteria due to its close structural similarities with the aurilides.…”
Section: Aurilides and Analoguesmentioning
confidence: 99%
“…As with aurilide, aurilides B and C showed significant in vivo antitumor activities based on NCI's hollow fiber assay. Kulokekahilide-2, a cytotoxin that is structurally related to aurilide, was isolated from the Hawaiian cephalaspidean mollusk Philinopsis speciosa [148,149]. The total synthesis of kulokekahilide-2 was completed, and SAR studies revealed that the chirality at the l-Ala and N-Me-d-Phe residues is essential for its potent cytotoxicity [150].…”
Section: Peptides and Depsipeptidesmentioning
confidence: 99%